Artritis Psoriatika - Rizki Ardhan, Faris; Akbar Hanardi, Muhammad; Thasliyah, Dhila; Vidyadevi Wiguna, Visakha; Putu Yunandari, Ni (Jurnal Syntax Fusion, 2021)
To know the risk factors, pharmacological treatment and prevention of psoriatic arthritis. Psoriatic arthritis is a chronic musculoskeletal disease associated with psoriasis. at least 5% of psoriasis patients develop psoriatic arthritis. Globally, the incidence of PsA reaches 133 per 100,000 patient subjects. The annual incidence of PsA is about 2.7 cases per 100 people diagnosed with psoriasis. In Asia, PsA cases increased from 2000 to 2013 with a prevalence (per 100,000 population) of 11.12 to 37.75. Based on a study at Sanglah Hospital Bali found PsA patients as much as 6.3% of psoriasis patients. PsA patients may have clinical features such as peripheral arthritis, enthesitis, dactylitis, skin, nail, and axial involvement. Risk factors for psoriatic arthritis include obesity, physical trauma, smoking, location of psoriasis in the body, education level and genetic factors. Pharmacological treatment of PsA based on the latest guidelines from EULAR 2019 and ACR recommendations. These two guidelines discuss pharmacological treatment based on the patient's clinical picture. The goal of pharmacological therapy is to improve the patient's quality of life by improving symptomatic complaints and preventing structural damage. As a prevention, PsA maintains an ideal body weight, reduces cigarette consumption, and performs detection as an early detection.